Introduction: Gascoigne from the Margins — Mediations, Translations, Appropriations - Bigliazzi, Silvia (Early Theatre, 2024)
This introduction presents the essays in the Early Theatre Issues in Review ‘Gascoigne from the Margins — Mediations, Translations, Appropriations’, placing them in the context of current criticism on Gascoigne and bringing them into a conversation on his dramatic works looked at from the ‘margins’.